Green synthesis of bimetallic Ag/Cu nanoparticle system using aqueous extracts of carica papaya and the investigation of water purification activity of the nanometals - Rosbero, Therese Marie S. (Animo Repository, 2016)
Nanoparticles, known for their unusual properties and remarkable applications in different fields, are usually synthesized through chemical methods. However, due to its various limitations, green route for nanoparticle synthesis is highly sought. This study aims to use aqueous leaf extracts of Carica papaya to synthesize Ag, Cu and bimetallic Ag/Cu nanoparticles. In this study, the synthesis of monometallic Ag & Cu nanoparticles was optimized first by varying time and temperature conditions. The color changes of each solution was monitored and nanoparticle formation was confirmed by the appearance of the AgNP surface plasmon resonance (SPR) in UV-Vis Spectroscopy. Optimization revealed that synthesis at 90°C for 2hrs generated higher yield, and this condition was used in the synthesis of bimetallic Ag/Cu nanoparticles. SEM characterization revealed the presence of aggregates and particles that are mutually varied in size. EDX analysis showed the presence of C, N, O, Ag & Cu in the sample. Among the synthesized bimetallic nanoparticles, only the Ag/Cu prepared from coreduction displayed a unique star-shaped structure with the observed average hydrodynamic particle size of 420.7 nm (DLS) and TEM size of ~30 nm. XRD patterns of Ag/Cu NPs displayed crystallinity with observed peaks corresponding to Ag, Ag2O and CuO. The synthesized AgNP & bimetallic Ag/Cu NPs were then utilized for degradation activity of the pesticide chlorpyrifos (CP) in water. The NPs were shown to effectively degrade CP affording less toxic degradation products as characterized by UV-Vis Spectroscopy and Liquid Chromatography-Mass Spectrometry. It is recommended that bimetallic Ag/Cu NPs be mapped with a high resolution microscopy and spectroscopy to determine its detailed structure. It is further recommended that the degradation activities of core-shell (Ag-Cu, Cu-Ag) NPs and physically mixed Ag & Cu NPs (Ag + Cu) be investigated for catalytic activities and for other applications.